Sex in the library a guide to sexual content in teen literature - Heller, Mary Jo (VOYA Press, 2013)
Sex in the Library is the ideal source for collection development of materials dealing with sex and sexuality for teens. Both public and school librarians will benefit from the guidance for establishing selection policies in this area and for sharing those policies with teachers, parents, administrators and teens. The book provides no-holds-barred and no-body-parts-left-out reviews of more than 100 books to be considered for collections. The reviews include ratings on sexual content, language, and violence as well as recommended age level and the use of "alert" words - words that often spark controversy. Readers also will appreciate as the ideas for educating students and adults about the mission statements of school and public libraries.